Acceleration capability in elite sprinters and ground impulse: Push more, brake less?. Issue 12 (18th September 2015) - Morin, Jean-Benoît; Slawinski, Jean; Dorel, Sylvain; de villareal, Eduardo Saez; Couturier, Antoine; Samozino, Pierre; Brughelli, Matt; Rabita, Giuseppe
Abstract: Overground sprint studies have shown the importance of net horizontal ground reaction force impulse ( IMP H ) for acceleration performance, but only investigated one or two steps over the acceleration phase, and not in elite sprinters. The main aim of this study was to distinguish between propulsive ( IMP H +) and braking ( IMP H − ) components of the IMP H and seek whether, for an expected higher IMP H, faster elite sprinters produce greater IMP H +, smaller IMP H −, or both. Nine high-level sprinters (100-m best times range: 9.95–10.60 s) performed 7 sprints (2×10 m, 2×15 m, 20 m, 30 m and 40 m) during which ground reaction force was measured by a 6.60 m force platform system. By placing the starting-blocks further from the force plates at each trial, and pooling the data, we could assess the mechanics of an entire "virtual" 40-m acceleration. IMP H and IMP H + were significantly correlated with 40-m mean speed ( r =0.868 and 0.802, respectively; P <0.01), whereas vertical impulse and IMP H − were not. Multiple regression analyses confirmed the significantly higher importance of IMP H + for sprint acceleration performance. Similar results were obtained when considering these mechanical data averaged over the first half of the sprint, but not over the second half. In conclusion, faster sprinters were those who produced the highest amounts of horizontal net impulse per unit body mass, and those who "pushed more" (higher IMP H +), but not necessarily those who also "braked less" (lower IMP H − ) in the horizontal direction.